Facile Synthesis of Functional Tricyclic Fused Furans by Intramolecular Wittig Reactions. Issue 21 (10th June 2013) - Tsai, Yi‐Ling; Das, Utpal; Syu, Siang‐en; Lee, Chia‐Jui; Lin, Wenwei
Abstract: A convenient protocol for the preparation of tricyclic fused furans in one step starting from acid chlorides and Michael acceptors is described. The reaction conditions are mild, operationally simple, and have a broad substrate scope. The reaction is believed to proceed by an intramolecular Wittig reaction with a phosphorus ylide as the key intermediate. Abstract : Functionalized fused furan derivatives were prepared in an intramolecular Wittig reaction in one step starting from simple and readily available substrates. The reaction is belived to proceed via an ylide intermediate. Furthermore, the products could be easily transformed into synthetically useful naphthofurans.